ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGUNJUNG MELALUI MINAT BERKUNJUNG SEBAGAI VARIABEL INTERVENING PADA KANTOR POS CABANG ASEMBAGUS - Pratama, Aldy Septyan; Hamdun, Edy Kusnadi; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The development of delivery services from year to year is increasingly becoming a concern of the wider community. Intense competition and the increasing number of delivery service companies that have sprung up at this time make the owner or manager must be able to create a strategy to be able to compete and be superior to his competitors. The purpose of this study is to determine the factors that influence visitor satisfaction through interest in visiting as an intervening variable at the Asembagus Branch Post Office. The population in this study were all visitors to the Asembagus Branch Post Office. Random sampling method (simple probability sampling) without regard to strata in the population in this study. Data analysis and hypothesis testing in this study used the Structural-partial Least square equation model (PLS-SEM). The results of the hypothesis test have a direct effect using the smart PLS 3.0 application, indicating that service quality has a significant positive effect on visiting interest. Location has a significant negative effect on interest in visiting. Service quality has a significant positive effect on visitor satisfaction. Location has a significant negative effect on visitor satisfaction. Interest in visiting consumers has a significant positive effect on visitor satisfaction. Service quality has a significant positive effect on visitor satisfaction through interest in visiting. Location has a significant negative effect on visitor satisfaction through interest in visiting.